At a meeting of the Committee of Observation for Lancaster County, May 1st, 1775 : Present. Edward Shippen, George Ross, Jasper Yeates . ([Printed by Francis Bailey], 1775)
Resolution calling for the formation of the Association of the Freemen and Inhabitants of the County of Lancaster to prepare for war by learning military science, and dividing into companies.